Optimization of the use of rollers in a banana farm A system simulation study - Hui, Peter John B. (2005)
A system simulation study on the use of rollers in the harvesting operations of Lapanday Farm 9 was done. It developed a simulation model of the harvesting operation of the farm were utilization of rollers occurs. The model allows simulation of different roller utilization combinations. It allows the viewing of possible results without actually implementing the combinations. It keeps track of combinations that allow optimal use of rollers in a harvesting operation. The model tested several roller utilization combinations on the five schedules of harvest from Monday to Friday, and with three conditions of total number available operational rollers divided equally among four teams, namely: 540,0560 and 580 rollers. With or without an increase in the total number of operational rollers, harvesting operation with optimal use of rollers can be achieved. Idle time is minimized as the number of loaded rollers in the initial delivery is increased. Eventually, it is eliminated as the number of loaded roller utilization combinations that have almost equal rollers in the initial and subsequent deliveries, and corresponding withdrawals. An ideal roller utilization combination is close to 55 rollers in initial and subsequent deliveries and 50 rollers in the corresponding withdrawals. The method used and the model developed is also useful for other farms with similar system of harvesting. These can be useful for farms that utilize contraptions like rollers that are cycled in the system and are not available in large numbers
Thesis (BS Applied Mathematics) -- University of the Philippines Mindanao, 2005